I & Claudius travels with my cat - De Vries, Clare (New York, NY Bloomsbury Distributed to the trade by St. Martin's Books, 1999)
A woman and her cat set off on a bold and hilarious adventure across the USA.
Map on endpapers
Keywords: De Vries, Clare -- Journeys; Claudius (Cat); United States -- Description and travel